Effects on Blood Pressure Control and Compliance for Medical Treatment in Hypertensive Patients by Sending Daily SMS as a Reminder - UZUNER, ARZU; AKMAN, MEHMET (DUZCE UNIV, 2017)
Objective: According to the World Health Organization(WHO), drug non-compliance in chronic diseases affects health conditions of patients negatively. The aim of this study is to determine the effects on blood pressure control and drug compliance in hypertensive patients by sending daily short message service(SMS). Methods: In this randomized controlled study, hypertensive patients were selected and divided into control and intervention groups. Daily SMS reminder has been send to intervention group for two months. Weekly ambulatory blood pressure measurements before two visits have been requested of all the patients and measurements were done at the visits. Compliance was scaled by Modified Morisky Questionnaire. Blood pressure measurements and compliance of each group was compared. Results: Sixty patients were enrolled in the study: 45 were female, 15 male; mean age was 55 +/- 11 years; mean BMI was 30 +/- 5 kg/m2; mean number of tablets per day was 4 +/- 2 pills. There was no statistically significant difference between the average at visit and weekly blood pressure (BP) measurements at first visit of two groups. The average at visit and weekly BP measurements at second visit were found to be statistically significant lower and the average at visit and weekly BP measurement change between first and second visit was found to be statistically significant higher in the intervention group compared to the control group. Drug compliance ratio was 36,7% for the control group, 96,7% for the intervention group. Conclusion: Sending a daily reminder SMS is effective in increasing blood pressure control and enhancing drug compliance in hypertension patients.
Keywords: Compliance; Antihypertensive; Sms; Blood Pressure; Hypertension; RANDOMIZED-CONTROLLED-TRIAL; IMPROVE ADHERENCE; CHRONIC DISEASE; INTERVENTIONS; HEALTH; IMPACT; MESSAGES; SERVICE